Teachers’ Knowledge Regarding Child Maltreatment in Elementary Schools at Mosul City /Iraq - Luay Amjed Mahmood Al-Waly; Iqbal Ghanim Ali Ma’ala (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: The study aim to assess the teachers knowledge level about child maltreatment in elementaryschools at Mosul city /Iraq.Methodology: A descriptive study design was chosen to fulfill the objectives of this research which wasconducted in sixty elementary schools inside of Mosul city/Iraq during the period from 1 October 2019till 30 May 2020. The study sample consists of (60) elementary schools teachers was selected by nonprobability(Purposive) sample from (60) schools inside Mosul city . The questionnaire data was filled bythe teachers in a face-to-face direct interview. Different statistical processing was conducted by the use ofversion 23 SPSS statistical packageResult: The result showed 63.3 % of teachers have poor knowledge regarding child maltreatment andthere is a significant relationship between the education levels of the elementary school teachers and theirknowledge about child maltreatment and there is no statistically significant relationship with other like thesocio-demographical variables.Conclusion: Need for enhancing teacher’s knowledge because the teachers in the elementary schools inMosul city do not have appropriate and adequate knowledge about child maltreatment.Recommendations: The researchers recommend design and implement different educational programs forteachers based on needs assessment concerning child maltreatment (e.g., definition, types, causes, signs/manifestations, methods like initial detection of a child at high risk, communication, management, etc.) topromote child health and development.